2011
DOI: 10.1111/j.1467-9671.2011.01257.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Participatory Computer Simulation to Explore the Process of Urban Evolution

Abstract: When planners intervene in urban systems they seek in part to generate a positive response from those parts of a city outside of their control, namely the private market and private individuals. This response is difficult to predict due to the fact that the city is a nonlinear system of organized complexity. Models of cities which seek to explain this response are necessarily complicated and dynamic. Where an analytical solution is not possible we turn to computer simulation and interactive visualization in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Then, policies can be formulated and tested in this simulated environment Geurts 2004, Greenblat andDuke 1981). Lately, games are usually constructed by combining sophisticated computer simulations with interaction and role play (Dearden and Wilson 2011). Simulations provide a realistic context to the policy being tested.…”
Section: Simulations In Urban Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, policies can be formulated and tested in this simulated environment Geurts 2004, Greenblat andDuke 1981). Lately, games are usually constructed by combining sophisticated computer simulations with interaction and role play (Dearden and Wilson 2011). Simulations provide a realistic context to the policy being tested.…”
Section: Simulations In Urban Planningmentioning
confidence: 99%
“…Scholars have suggested that integrated frameworks and methods that support participatory processes in the context of realistic explorations of the complex dynamics of systems and of different data sets are the best ways forward for planning support (Dearden and Wilson 2011, Devisch 2012, Bueren 2009). Such frameworks are needed to further develop methodologies.…”
Section: Introductionmentioning
confidence: 98%
“…Lately, games are usually constructed by combining sophisticated computer simulations with interaction and role play (Dearden and Wilson 2011). Simulations provide a realistic context to the policy being tested.…”
Section: Gaming Simulation In Urban Planningmentioning
confidence: 99%
“…The participatory approach focuses on politics and process, and tends to neglect scientific facts as described by models. The best way forward are mixed methods which integrate advanced computer simulations with collaborative processes, referencing both the dynamics of underlying systems as well as the political dimensions of planning (Van Bueren 2009;Dearden and Wilson 2011). Collaborative decision support systems, participatory simulations and gaming simulations have all been used as such mixed methods (Devisch 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Topics that are presented by participatory simulations include, e.g., beehives, pandemics or global warming. While engaging in a participatory simulation, students' learning can be enhanced through constant reflections on their experiences in both real‐world and virtual simulations (Dearden & Wilson, 2011; Dede, 2005; Klopfer & Squire, 2008). Moreover, participatory simulations can best support learning by allowing students to actively and collaboratively search for and create learning experiences, rather than passively accepting and absorbing information from a single source (Dede, 2005; Ke & Carafano, 2016).…”
Section: Introductionmentioning
confidence: 99%